2012
DOI: 10.1007/978-3-642-33709-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Depth Matters: Influence of Depth Cues on Visual Saliency

Abstract: Most previous studies on visual saliency have only focused on static or dynamic 2D scenes. Since the human visual system has evolved predominantly in natural three dimensional environments, it is important to study whether and how depth information influences visual saliency. In this work, we first collect a large human eye fixation database compiled from a pool of 600 2D-vs-3D image pairs viewed by 80 subjects, where the depth information is directly provided by the Kinect camera and the eye tracking data are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
147
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(156 citation statements)
references
References 26 publications
1
147
2
Order By: Relevance
“…Our work contrasts with [14] through the additional observations on depth saliency reported from our experiments, through the formulations of our 3D saliency model and the model for fusing 3D and visual saliency. It is well known that in images of large depth of field scenes taken using conventional cameras, the farther regions are out-of-focus, but images from the Kinect camera does not contain this phenomenon.…”
Section: Introduction and Related Workmentioning
confidence: 90%
See 2 more Smart Citations
“…Our work contrasts with [14] through the additional observations on depth saliency reported from our experiments, through the formulations of our 3D saliency model and the model for fusing 3D and visual saliency. It is well known that in images of large depth of field scenes taken using conventional cameras, the farther regions are out-of-focus, but images from the Kinect camera does not contain this phenomenon.…”
Section: Introduction and Related Workmentioning
confidence: 90%
“…With the advent of the Kinect sensor, depth information has been used in addition to color images for object recognition [13], human action recognition [22] and saliency detection [14,16,18]. In [18] and [16] , authors incorporate depth information from stereopsis making use of disparity maps of saliency detection.…”
Section: Introduction and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Lang et al present a depth prior for saliency learned from human gaze information [16]. This saliency prior produces a saliency map that is then either directly added or multiplied by the saliency results of other methods.…”
Section: Saliency Computation With Depthmentioning
confidence: 99%
“…We propose a novel method which incorporates depth measurements into the computation of visual saliency. Human subject studies have shown that depth is an important cue in determining salient regions in human visual processing [16,23]. Depth measurements make it possible to separate objects which may be similar in appearance.…”
Section: Introductionmentioning
confidence: 99%